Seasonal suitability of three rubber tree clones to Calacarus heveae (Acari, Eriophyidae) - Daud, Rodrigo Damasco [UNESP]; Fazzio Feres, Reinaldo Jose [UNESP]; Hernandes, Fabio Akashi [UNESP] (Springer, 2012)
The suitability of rubber tree clones to Calacarus heveae was inferred from the life cycle, reproduction and survivorship of this mite. The assays were performed under controlled conditions with leaflets detached from 6-year-old plants. The development of 20 C. heveae individuals on each of the clones GT 1, PB 235 and RRIM 600 was analysed. This experiment was performed four times during periods when C. heveae was abundant in the field: (P1) November-December 2005, (P2) January-February, (P3) March-April and (P4) May-June 2006. Accordingly, the leaflets used in each assay represented the physiological condition of the host plant during each period. This approach allowed us to evaluate the seasonal suitability of rubber tree clones to C. heveae. We observed seasonal differences in the suitability of rubber tree clones to mite attack. The mites reared on the PB235 had a shorter development period, the highest egg production and highest survivorship. This evidence showed that the PB 235 was the most suitable of those tested. We also observed that the leaflets used in the assays during periods P2 and P3 were the most favourable for the development of C. heveae. This finding emphasises the seasonal suitability of rubber tree leaflets. on the other hand, GT 1 showed higher resistance against C. heveae than did RRIM 600 and PB 235, primarily during the period from November to February. This result indicated that use of the GT 1 clone to control the mite might represent an alternative for growers.
Keywords: Biology; Hevea brasiliensis; Life cycle; Phytophagous mites; Resistance